PENYELESAIAN TINDAK PIDANA PENCURIAN ALIRAN LISTRIK DI LUAR PENGADILAN BERDASARKAN UNDANG-UNDANG NOMOR 30 TAHUN 2009 TENTANG KETENAGALISTRIKAN DI WILAYAH HUKUM TAPUNG KABUPATEN KAMPAR - VANDIWINATA, YULI; ', Erdianto; Edorita, Widia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
Control of Electricity Usage (P2TL) according to Article 1 number 18 Decree of the Board of Directors of PT PLN (Persero) No.68.K / 010 / DIR / 2000 is an inspection by PLN of PLN installations and customer installations in order to Control Electricity Usage. In practice, criminal acts in the electricity sector, especially those involving electricity theft, are not resolved through court institutions but through institutions outside the court. This condition does not make deterrent actors repeat it and even invite other actors to do it. The purpose of writing this thesis is to explain the reasons for conducting an off-court settlement of a crime of theft of electric current, a settlement mechanism carried out by PT PLN and the legal consequences of an off-court settlement of a crime of theft of electric current. To obtain data in this thesis writing, literature research and field research are conducted. Library research is conducted to obtain secondary data, while field research is conducted to obtain primary data through interviews with respondents and informants. The results of the research show that the reason for the non-court settlement of the crime of electric current theft is because PT PLN (Persero) which is controlling the Electricity Usage Control Team (P2TL) is more focused on efforts to avoid conflict with the community and seek compensation for finance production.The mechanism for resolving criminal acts of theft of electric current by PT PLN customers is carried out through P2TL officers who come to the location of the violation or the illegal use of electricity (theft) to terminate the temporary electricity connection and submit a supplementary bill. If the offender carries out his obligation to pay the bill then the electricity will be reconnected. As a result of the law of non-court settlement of this case is the existence of an off-court settlement, then the crime of theft of electric current is erased and if the perpetrator has carried out a bill payment, the customer can return to PT PLN customer as before. It is advisable for policy makers to be able to issue more stringent legal regulations regarding legal sanctions for perpetrators of the use of electricity asrus users / users in order to avoid customer actions to repeat their actions which could harm PT PLN in the future. It is recommended to the PLN to continue to control efforts to avoid the existence of other actors who use electricity illegally that can harm PT PLN and also other customers who become consumers of electricity